Studies on Schismatoglottideae (Araceae) of Borneo XXXI - Piptospatha insignis re-found - Boyce, P.C; Wong, Sin Yeng (International Aroid Society, Inc., 2013)
Piptospatha insignis N.E. Br. has been re-found in the wild in Lawas District, Limbang Division, Sarawak, Malaysian Borneo for the first time since its discovery (at an unspecified North Bornean location) by Frederick Burbidge sometime between 1877 and 1878. A modified species description and photographs of the living plant and reproductions of the original illustrations are presented.